Žepnina kot sredstvo proti revščini in socialni izključenosti mladostnikov in mladostnic - Jerant, Jasmina (Socialno delo, 2020)
The 15-17 years old youngsters are at the greatest risk of poverty and social exclusion among all European children. Lacking economic resources deepens their social exclusion which negatively impacts their social capital and traps them in poverty. Public policy of a financial aid (in form of pocket money) to teenagers living in poverty is therefore a tool of social justice. Ten in-depth interviews with Slovenian teenagers who received such a cash benefit through a charity project called Godparenting reveal that such a monetary transfer in the name of social justice aids in battling social exclusion even in case of small things like coffee with peers, as it positively impacts subjective well-being, self-esteem and strengthens social capital. Thus it alleviates poverty on a long term. Considering that the cash transfer teenagers receive is only 30 euros a month, it would be important to think of a higher financial help which would even enlarge the opportunities of children living in poverty. Noteworthy is also the finding that the recepients are, despite being happy to receive it, ashamed of the cash transfer in question, making this research an argument for the Universal Basic Income.
Keywords: adolescenca; adolescence; cash transfers; denarna socialna pomoč; enake možnosti; equal opportunities; social equality; social inclusion; social justice; socialna enakost; socialna pravičnost; socialna vključenost